2013
DOI: 10.3174/ajnr.a3496
|View full text |Cite
|
Sign up to set email alerts
|

What Is Meant by “TICI”?

Abstract: Our aim is to review how subsequently published studies define TICI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(77 citation statements)
references
References 73 publications
0
70
0
1
Order By: Relevance
“…The TICI scale has many variations,19 but the most widely referred to are Higashida's original version8 and mTICI proposed by Tomsick et al ,18 which draw the boundaries between TICI 2a and TICI 2b at 66% and 50% reperfused territory, respectively. Both versions show comparable interobserver agreement and provide a valid and clinically relevant assessment of ‘success’—as multiple studies reported substantial differences in outcome between TICI 2a and TICI 2b11 for either version of the scale 10.…”
Section: Discussionmentioning
confidence: 99%
“…The TICI scale has many variations,19 but the most widely referred to are Higashida's original version8 and mTICI proposed by Tomsick et al ,18 which draw the boundaries between TICI 2a and TICI 2b at 66% and 50% reperfused territory, respectively. Both versions show comparable interobserver agreement and provide a valid and clinically relevant assessment of ‘success’—as multiple studies reported substantial differences in outcome between TICI 2a and TICI 2b11 for either version of the scale 10.…”
Section: Discussionmentioning
confidence: 99%
“…In the 17 recent studies regarding intra-arterial thrombolysis in acute posterior circulation stroke, 13 30 Therefore, selection of a reliable biomarker for revascularization is relevant to the prediction of procedural efficacy and the outcome in posterior circulation stroke. To our knowledge, this is the first study to evaluate inter-and intraobserver agreement for 2 common scales in the angiographic evaluation following intra-arterial thrombolysis of posterior circulation stroke.…”
Section: Discussionmentioning
confidence: 99%
“…A Thrombolysis in Cerebral Infarction (TICI) score of 3 is the desired result of endovascular AIS treatments, and is assessed when complete perfusion is achieved, without clot fragmentation and distal embolization. Although the success of endovascular revascularization is often assessed by a variety of angiographic grading systems,24 25 small microemboli may not be seen on imaging, and their effect on the clinical outcomes may be underestimated.…”
Section: Discussionmentioning
confidence: 99%